MAXIMUM CRIMINAL SANCTIONS FOR THE PERSONNEL OF Rape ACCORDING TO ARTICLE 285 KHUP (Case Study of Decision Number 131 / Pid.B / 2019 / PN.Cbi) - Pitriadin, Pitriadin; Usmanilala, Usmanilala (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
The research objective was to analyze and describe the provision of non-maximum criminal sanctions for perpetrators of the crime of rape according to Article 285 KHUP in Decision Number 131 / Pid.B / 2019 / PN.Cbi and to analyze and describe judges' considerations in deciding cases of rape in decision No. 131 / Pid.B / 2019 / PN.Cbi. The research method used is the method of data analysis and library research / normative legal research, including primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study show that the imposition of criminal sanctions is not maximum for the perpetrators of the crime of rape in Decision Number 131 / Pid.B / 2019 / PN.Cbi has not provided a sense of justice for victims because in practice law enforcement officials including the panel of judges who should be a mouthpiece of justice turned out to be did not give maximum sanctions to the perpetrators, the panel of judges in the case even openly ignored the condition of victims who had experienced trauma and depression. This provides clear evidence that there is still a lack of guaranteed protection for victims of sexual violence, especially rape in Indonesian criminal justice. Judges considerations in deciding criminal cases of rape in decision No. 131 / Pid.B / 2019 / PN.Cbi which imposes imprisonment for 3 (years), namely when the perpetrator is aware of the consequences, the perpetrator is in a healthy condition and is capable of considering his actions. The judge also did not see any justification or excuse reasons which could be the reason for the elimination of the criminal offense committed by the perpetrator. The Panel of Judges only saw incriminating matters, namely the perpetrator's actions which made witness Erica Alendha Sari experience psychological trauma. In this case the judge did not consider guaranteeing the fulfillment of the rights of victims of sexual violence, especially rape, for remedy that must be accommodated at every stage of the criminal justice system. For this reason, it is necessary to formulate laws and regulations that guarantee the fulfillment of the right to treatment including the right to confidentiality of identity, the right to protection related to guarantees of not being blamed and prosecuted for their testimony and also the right to recovery for victims of violence so that they can continue their life.